Work participation and employment in individuals with cerebral palsy: A scoping review - Ilse M. van Rijssen; Ivana Bardino Novosel; Emmeke Faas; Manin Konijnenbelt; Jan Willem Gorter; Johanna M. A. Visser‐Meily; Olaf Verschuren (Developmental Medicine & Child Neurology, 2026)
Abstract Aim To map factors related to employment in adults with cerebral palsy (CP), summarize evidence on barriers and facilitators, and identify gaps in existing literature. Method A scoping review was conducted in accordance with the JBI. A systematic search across five databases up to 22nd March 2026 identified 29 studies including 33 069 adults with CP. The outcome of interest was paid employment and employment dropout in adults with CP. Factors were categorized using the International Classification of Functioning, Disability and Health (ICF) framework. Results Twenty‐one studies addressed body functions and structures (e.g. intelligence, dexterity), 11 focused on activities (e.g. Gross Motor Function Classification System level, independence), five on participation (e.g. communication), 13 on environmental factors (e.g. accessibility, support), and 20 on personal factors (e.g. age, education). Methodological quality varied, with many studies rated low to moderate. Interpretation Employment among adults with CP is shaped by interrelated factors across ICF domains. Research gaps include limited attention to environmental and personal factors, underrepresentation of adults over 40 years of age, and lack of longitudinal studies. Addressing these gaps and learning from other populations is essential to improve vocational support.